Papillon-Lefevre syndrome: Reporting consanguinity as a risk factor - Aasim Farooq Shah; Pradeep Tangade; Swatantra Agarwal (Elsevier, 2014)
Papillon-Lefevre syndrome (PLS) is an autosomal recessive genetic disorder characterized by palmoplantar hyperkeratosis associated with severe early-onset periodontitis and premature loss of primary and permanent teeth. This report describes two cases of PLS in 28-year-old female and 16-year-old male siblings with consanguineously married parents. The patients presented to the Department of Public Health Dentistry of a dental education and research institute in India with thickening, flaking, and scaling of the skin on the palms and soles of the feet. On oral examination, the female patient presented completely resorbed maxillary and mandibular alveolar ridges with retention of only the third molars. The male patient retained only teeth 18, 13, 28, 38, and 45. Based on complete histories and clinical examination findings, a final diagnosis of PLS was made and treatment was initiated using an interdisciplinary dental approach in both cases. Keywords: Papillon-Lefevre syndrome, Consanguinity, Periodontitis, Premature tooth loss